A formação de professores de Educação Física para a Diversidade Cultural - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This study addresses the importance of cultural diversity in an ever-changing world and underscores the need for education that fosters understanding and respect for diversity. With increasing diversity in schools, there is a demand for more competent teachers in this context. However, many teachers are unprepared to handle this diversity after initial training, and continuing education courses have also failed in this regard. The research aims to understand the characteristics of Physical Education (PE) teacher training courses that enhance their cultural competencies. Specific objectives include: 1) assessing the demands of historically marginalized groups and their impact on Brazilian educational policies; 2) understanding the research field of teacher training and cultural diversity to set parameters for future research; 3) identifying the characteristics of effective PE teacher training courses for developing the necessary teaching competencies in culturally diverse environments. The research followed a multipaper format to conduct three literature reviews, each addressing one of the specific objectives. The first study evaluated the Brazilian educational policy agenda regarding cultural diversity, highlighting the need to empower policies for cultural diversity with the participation of historically marginalized groups in policy- making bodies. The second study conducted a bibliometric analysis, revealing the current stage of evolution in the research field of teacher training and cultural diversity. It identified key journals, authors, countries, and articles in the sample, as well as the intellectual and conceptual structure of the field. The third study constructed the state of knowledge on PE teacher training and cultural diversity using the Methodi Ordinatio 2.0 workflow. The meta-synthesis of knowledge identified contexts, justifications, designs, methods, data collection instruments, and sample characteristics in the analyzed articles. It highlighted six characteristics of effective PE teacher training courses for promoting cultural competencies: 1) critical and reflective approach to sociocultural issues; 2) inclusion of relevant diversity content; 3) practical experiences in diverse contexts; 4) curricular space for cultural competency development; 5) support and mentorship for teachers in training; 6) continuous evaluation of cultural competencies.
Keywords: Formação de professores; Diversidade Cultural; Multiculturalismo; Interculturalismo; Educação Física; Teacher education; Cultural Diversity; Multiculturalism; Interculturalism; Physical Education; CNPQ::CIENCIAS SOCIAIS APLICADAS